The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1128/jcm.00469-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Helicobacter pylori cagA andvacAGenotypes among Alaskans and Their Correlation with Clinical Disease

Abstract: Helicobacter pylori infection is common in Alaska. The development of severe H. pylori disease is partially determined by the virulence of the infecting strain. Here we present vacA and cagA genotype data for H. pylori strains isolated from Alaskans and their correlation with clinical disease. We enrolled patients scheduled for esophagogastroduodenoscopy and positive for H. pylori infection. Gastric biopsy specimens from the stomach antrum and fundus were cultured. We performed PCR analysis of the H. pylori va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
48
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 48 publications
15
48
1
Order By: Relevance
“…babA2 were associated with peptic ulcer. The correlation of such clinical manifestation with these genotypes is consistent with earlier studies [35,41,52]. This is explained by the higher virulence and mucosal injury determined by such strains.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…babA2 were associated with peptic ulcer. The correlation of such clinical manifestation with these genotypes is consistent with earlier studies [35,41,52]. This is explained by the higher virulence and mucosal injury determined by such strains.…”
Section: Discussionsupporting
confidence: 91%
“…The H. pylori vacA s1m1 genotype is the most common in American, European and East Asian countries [24,29,[41][42][43]. The vacA s2m2 genotype is apparently less common and another study in Portugal, performed in patients submitted to a screening program, revealed a prevalence of 29.7 % for such allele combination (42.9 % if multiple vacA genotypes were excluded).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progression from normal tissue to cancerous tissue is thought to be a change from acute gastritis to chronic gastritis to IM to cancer [44,45]. The association seen here, between cagPAI and both IM and moderate–severe acute antral gastritis, agrees with previous reports that have shown an intact element is related to more severe disease [7,11,12,21,4648]. A previous study in Alaska Native people found that over 90% of both individuals with gastric cancer and healthy individuals had antibodies against the CagA protein[19], indicating that exposure to bacteria expressing and exporting this protein is very common.…”
Section: Discussionsupporting
confidence: 89%
“…During the EGD, gastric biopsy specimens were also collected for H. pylori culturing and genotyping, as previously described [21,22]. PCR analysis was performed on H. pylori DNA extracts to detect the presence of the right and left ends of the cagPAI , as well as the cagA, cagE, cagT , and virD4 genes (Supplemental Table 1).…”
Section: Methodsmentioning
confidence: 99%